2014
DOI: 10.1039/c3dt53000k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, stereocontrol and structural studies of highly luminescent chiral tris-amidepyridyl-triazacyclononane lanthanide complexes

Abstract: (2014) 'Synthesis, stereocontrol and structural studies of highly luminescent chiral tris-amidepyridyl-triazacyclononane lanthanide complexes. ', Dalton transactions., 43 (14). pp. 5490-5504. Further information on publisher's website:http://dx.doi.org/10.1039/C3DT53000KPublisher's copyright statement: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…13,15,16 These structural studies also confirmed that the phosphorus-oxygen double bond lies out of the plane of the aryl rings. A simple retrosynthetic analysis suggests the intermediacy of a 2,4,6-trisubstituted pyridine, with a 4-Br group, allowing a Sonogashira coupling reaction to an arylalkyne in a final ligand assembly step.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…13,15,16 These structural studies also confirmed that the phosphorus-oxygen double bond lies out of the plane of the aryl rings. A simple retrosynthetic analysis suggests the intermediacy of a 2,4,6-trisubstituted pyridine, with a 4-Br group, allowing a Sonogashira coupling reaction to an arylalkyne in a final ligand assembly step.…”
Section: Resultssupporting
confidence: 54%
“…the P centres respectively, as deduced by X-ray and CD studies on related systems. [13][14][15][16] OBC 2014 Delbianco 3…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, brightness in the range 20 000-30 000 M -1 cm -1 has recently been achieved in aqueous solution for Eu III complexes [22]. Scheme 1.…”
Section: Lanthanide Luminescent Probes: the Toolkitmentioning
confidence: 99%